2009
DOI: 10.1111/j.1551-2916.2009.03092.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorus Impurity on Tricalcium Silicate T1: From Synthesis to Structural Characterization

Abstract: Alite is the major compound of anhydrous Portland cement: it is composed of tricalcium silicate Ca3SiO5 (C3S) modified in composition and crystal structure by ionic substitutions. Alite is also the main hydraulic phase of cement and the most important for subsequent strength development. Using raw meals (rich in Ca3P2O8) as alternative fuels in cement plants raises the question about the effect of phosphorus on C3S and its consequences on reactivity with water. This paper deals with a systematic study of C3S t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
4
23
0
Order By: Relevance
“…First, C 2 S-C 3 P solid solutions such as Ca 2 SiO 4 ·0.05Ca 3 (PO 4 ) 2 and Ca 15 (PO 4 ) 2 (SiO 4 ) 6 were detected in the XRD pattern of RMCr. This phenomenon was similar to what was observed by Marie-Noe¨lle de Noirfontaine [38], who reported that adding phosphorus could cause partial decomposition of C 3 S into C 2 S and CaO phases, and that phosphorus was present in solid solution phases of C 2 S-C 3 P. Second, in the clinker samples of RMNi and RMCu, phosphorus was also present in such heavy metal-containing compounds as K 2 NiP 2 O 7 , K 2 Cu(PO 3 ) 4 , and Cu 4 O(PO 4 ) 2 . This indicates that parts of Cu and Ni were not incorporated in the calcium silicate phases but that they reacted with P and alkali metals.…”
Section: Impact Analysis Of Municipal Sewage Sludge On Incorporating supporting
confidence: 76%
“…First, C 2 S-C 3 P solid solutions such as Ca 2 SiO 4 ·0.05Ca 3 (PO 4 ) 2 and Ca 15 (PO 4 ) 2 (SiO 4 ) 6 were detected in the XRD pattern of RMCr. This phenomenon was similar to what was observed by Marie-Noe¨lle de Noirfontaine [38], who reported that adding phosphorus could cause partial decomposition of C 3 S into C 2 S and CaO phases, and that phosphorus was present in solid solution phases of C 2 S-C 3 P. Second, in the clinker samples of RMNi and RMCu, phosphorus was also present in such heavy metal-containing compounds as K 2 NiP 2 O 7 , K 2 Cu(PO 3 ) 4 , and Cu 4 O(PO 4 ) 2 . This indicates that parts of Cu and Ni were not incorporated in the calcium silicate phases but that they reacted with P and alkali metals.…”
Section: Impact Analysis Of Municipal Sewage Sludge On Incorporating supporting
confidence: 76%
“…Since the 1990s, the cement industry has used more and more alternative fuels (ratio up to 1/3), in order to favour the valorization of wastes and reduce the use of fossil fuels. This was the origin of new experimental studies related to the effects of minors, such as phosphorus when meat and bone meals are burnt [7]. These studies highlight the lack of knowledge of multi-component equilibrium phase diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the α′-belite phase is stabilized by P 2 O 5 (39,40) and concentration of up to 1.0% P 2 O 5 by mass in the clinker do not have an adverse effect on its properties (40). In this work the concentrations of the phosphate in the three clinkers is below 1% and lay in the range of 0.11-0.17%.…”
Section: Discussionmentioning
confidence: 99%